Primary thyroid lymphoma (PTL): A rare case report and review of the literature - Luan, Dao Thi; Quynh, Nguyen Thi; Yen, Do Thi (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2022)
Primary thyroid lymphoma (PTL) is a rare malignancy of the thyroid, accounting for 5% of all thyroid malignancies and approximately 2% of extranodal lymphomas. PTL occurs mainly in elderly females and diffuse large B-cell lymphoma (DLBCL) is most common. Here we report a case of non-germinal center diffuse large B-cell lymphoma (non - GC DLBCL) occurring in a 62 - year - old female who was admitted to the hospital because of multiple palpable left neck masses. The patient then underwent thyroid ultrasound, detecting multiple nodules in the two lobes and isthmus of the thyroid gland, in which the largest nodule was in the left lobe with TIRADS 5 measuring 47x33 mm, and many cervical lymph nodes. Microscopically, thyroid tissue showed proliferation of tumor cells with large nuclei, coarse chromatin, narrow rims of cytoplasm, and scattered mitoses. There was 01 destructured lymph node, proliferating cells with characteristics similar to those in the thyroid gland; the remaining lymph nodes were chronically inflamed. Immunohistochemically, the tumor cells were positive for CD20, CD79a, Ki67 (40%), and negative for CD10, BCL6, MUM1, CD5, BCL2, cMYC, CD15, CD30, EBV. Primary thyroid lymphomas are rare with the prognosis of patients depending on the histological classification of the tumor and the stage of the disease. They need to be evaluated and treated individually because there is no unified treatment due to their rarity